A Comparison of Petiole Hydraulics and Aquaporin Expression in an Anisohydric and Isohydric Cultivar of Grapevine in Response to Water-Stress Induced Cavitation - Shelden, Megan C.; Vandeleur, Rebecca; Kaiser, Brent N.; Tyerman, Stephen D. (Frontiers in Plant Science, 2017)
We report physiological, anatomical and molecular differences in two economically important grapevine (Vitis vinifera L.) cultivars cv. Grenache (near-isohydric) and Chardonnay (anisohydric) in their response to water-stress induced cavitation. The aim of the study was to compare organ vulnerability (petiole and stem) to cavitation by measuring ultrasonic acoustic emissions (UAE) and percent loss of conductance of potted grapevines subject to the onset of water-stress. Leaf (ψL) and stem water potential (ψS), stomatal conductance (gs), transpiration (E), petiole hydraulics (KPet), and xylem diameter were also measured. Chardonnay displayed hydraulic segmentation based on UAE, with cavitation occurring at a less negative ψL in the petiole than in the stem. Vulnerability segmentation was not observed in Grenache, with both petioles and stems equally vulnerable to cavitation. Leaf water potential that induced 50% of maximum UAE was significantly different between petioles and stems in Chardonnay (ψ50Petiole = -1.14 and ψ50Stem = -2.24 MPa) but not in Grenache (ψ50Petiole = -0.73 and ψ50Stem = -0.78 MPa). Grenache stems appeared more susceptible to water-stress induced cavitation than Chardonnay stems. Grenache displayed (on average) a higher KPet likely due to the presence of larger xylem vessels. A close relationship between petiole hydraulic properties and vine water status was observed in Chardonnay but not in Grenache. Transcriptional analysis of aquaporins in the petioles and leaves (VvPIP1;1, VvPIP2;1, VvPIP2;2 VvPIP2;3, VvTIP1;1, and VvTIP2;1) showed differential regulation diurnally and in response to water-stress. VvPIP2;1 showed strong diurnal regulation in the petioles and leaves of both cultivars with expression highest predawn. Expression of VvPIP2;1 and VvPIP2;2 responded to ψL and ψS in both cultivars indicating the expression of these two genes are closely linked to vine water status. Expression of several aquaporin genes correlated with gas exchange measurements, however, these genes differed between cultivars. In summary, the data shows two contrasting responses in petiole hydraulics and aquaporin expression between the near-isohydric cultivar, Grenache and anisohydric cultivar, Chardonnay.